Slovensko podjetništvo v letu krize: GEM Slovenija 2009 - Rebernik, Miroslav; Tominc, Polona; Pušnik, Ksenja (2010)
Slovenian Entrepreneurship in the Year of Crisis : GEM Slovenia 2009. Global Entrepreneurship Monitor (GEM) – the world’s most comprehensive research on entrepreneurship – focuses on an individual and the entire spectrum of factors influencing the relationships between entrepreneurs, entrepreneurship and society and its development. Enterprises are created by individuals while the individual’s inclination towards entrepreneurship is shaped by a number of factors of a country’s institutional framework, the attitude of a society towards entrepreneurship, cultural values, etc. These factors differ according to the level of the individual country’s economic development. The role of entrepreneurship differs in each of these types of economies, which, consequently, requires a different response by the bodies in charge of economic policy and promotion of entrepreneurship. The monograph at hand thus includes a number of analyses comparing the Slovenian economy with these three types of economies. The analyses mainly concentrate on the countries with economic development similar to Slovenia’s or on the ones which are geographically closer. A short chapter of the monograph is devoted to Global Entrepreneurship Index (GEI). This index enables a separate observation of three key categories of entrepreneurship in an individual country (entrepreneurial attitudes, entrepreneurial activity and entrepreneurial aspirations), which can in turn be compared globally. In 2009, also social entrepreneurship was included in the research for the first time.
Keywords: podjetništvo; podjetniška aktivnost; Globalni podjetniški indeks; gospodarska kriza; socialno podjetništvo; Entrepreneurship; Entrepreneurial Activity; Global Entrepreneurship Index; Economic Crisis; Social Entrepreneurship